x − 1 lo g 2 ( x + 1 ) > 0
State the domain of the inequality above.
The following answer can be written in the form x ∈ ( a , b ) ∪ ( c , ∞ ) .
Find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I know it is a long solution and it can be done in a shorter way, but since the shorter way has already been posted, I have posted the long algebraic approach.
Let's take 3 cases.
Case 1: x+1>1 ( ∴ x ∈ ( 0 , ∞ ) )
x − 1 lo g 2 ( x + 1 ) > 0
Since numerator of LHS is positive, the denominator should be positive too.
∴ x-1>0
∴ x>1 ( ∴ x ∈ ( 1 , ∞ ) )
x ∈ ( 0 , ∞ ) ∩ ( 1 , ∞ ) ⇒ x ∈ ( 1 , ∞ ) for x+1>1
Case 2: x+1<1 ( ∴ x ∈ ( − ∞ , 0 ) )
x − 1 lo g 2 ( x + 1 ) > 0
Since numerator of LHS is negative, the denominator should be negative too.
∴ x-1<0
∴ x<1 ( ∴ x ∈ ( − ∞ , 1 ) )
x ∈ ( − ∞ , 0 ) ∩ ( − ∞ , 1 ) ⇒ x ∈ ( − ∞ , 0 ) for x+1<1
Case 3: x+1=0
x − 1 lo g 2 ( x + 1 ) > 0
x − 1 lo g 2 ( 1 ) > 0
0 > 0
∴ x ∈ ϕ for x+1=0
Taking union of all cases:
x ∈ ( − ∞ , 0 ) ∪ ( 1 , ∞ )
Now we look at the conditions.
Condition 1: x+1>0 (because it is in the logarithm)
x+1>0
∴ x>-1
∴ x ∈ ( − 1 , ∞ )
Condition 2: x-1 = 0
∴ x = 1
∴ ( − ∞ , 1 ) ∪ ( 1 , ∞ )
Intersecting cases and conditions, we get:
∴ x ∈ [ ( − ∞ , 0 ) ∪ ( 1 , ∞ ) ] ∩ ( − 1 , ∞ ) ∩ [ ( − ∞ , 1 ) ∪ ( 1 , ∞ ) ]
∴ x ∈ ( − 1 , 0 ) ∪ ( 1 , ∞ )
So, -1 is the incorrect solution. But if we ignore the ( 1 , ∞ ) part, we get-
− 1 + 0 = − 1
Ur approach is very long. I solved it in 5 sec. It was very easy to detect critical points.
Log in to reply
Even I solved it mentally in 5 secs, but since the shorter way has been posted, I have posted a long way
What I did is this.
Case 1: numerator, p ( x ) and denominator, q ( x ) such that p ( x ) > 0 , q ( x ) > 0
p ( x ) > 0 ⇒ l o g 2 ( x + 1 ) > 0 ⇒ x > 0 or x ∈ ( 0 , ∞ ) q ( x ) > 0 ⇒ x − 1 > 0 ⇒ x > 1 or x ∈ ( 1 , ∞ )
Hence x ∈ ( 1 , ∞ ) ∩ ( 0 , ∞ ) ⇒ x ∈ ( 1 , ∞ )
Here's the fun part:
Case 2: numerator, p ( x ) and denominator, q ( x ) such that p ( x ) < 0 , q ( x ) < 0
p ( x ) < 0 ⇒ l o g 2 ( x + 1 ) < 0 ⇒ x ∈ ( − 1 , 0 ) q ( x ) > 0 ⇒ x − 1 < 0 ⇒ x < 1 or x ∈ ( − ∞ , 1 )
Hence x ∈ ( − 1 , 0 ) ∩ ( − ∞ , 1 ) ⇒ x ∈ ( − 1 , 0 )
Note that ( − 1 , 0 ) = ( a , b ) , therefore a + b = − 1 + 0 = − 1
We are done!
Problem Loading...
Note Loading...
Set Loading...
Just find the critical points. they are 0 a n d 1
solve using wavy curve u get ( − ∞ , 0 ) and ( 1 , ∞ )
Also the argument of logarithm i.e. x + 1 > 0
taking the intersection of all values, the answer is ( − 1 , 0 ) U ( 1 , ∞ )